19th Annual Fresno County Legal Secretaries Association Annual Bosses' Night Honoring Gaspar Magarian - Watkins, Howard::::::::: (1987)
Fresno County Legal ServicesA President Mildred Christian, Fresno County Bar Association President Howard Watkins holding raffle prize and California Legal Secretaries, Inc. President Joyce Seymour